Outcome of Unengaged Fetal Head at Term in Nullipara - Bibi Sara, Farkhanda Sadiq, Saira Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Engagement of fetal head is usually regarded as a phenomenon of labor in nullipara. It commonly occurs during the last few weeks in nullipara, in majority by 38 weeks or even during the first stage of labor. The aim of this study was to determine the outcome of unengaged fetal head at term in nullipara. Materials And Methods: This study was conducted at obstetrics and gynecology unit, tertiary care teaching hospital, Peshawar. This was a descriptive cross-sectional study which was conducted during 12th Jan 2021 to 10th April 2022, in which a total of 111 patients were included in the study using 16.89% proportion of caesarean section¸95% confidence level and 7% margin of error under WHO software for sample size determination. Results: In this study, patients were in age range 19-35 years and heights of the patients were 140-160cm. Among 111 patients, normal vaginal delivery occurred in 71.71% patients, instrumental delivery in 10.8% and 18.2% patients underwent low segment caesarean section. Total number of nullipara with unengaged head were divided into four groups based on fetal head station in early labor. Total number of nullipare in each group of which 30.6% were free head, 43.2% at -3 station group, 21.62%-2 station group and 45% in -1 group Practical implication in nulliparous patients a high station at the onset of labour is not necessarily an omnious finding, even though the incidence of arrest disorders are higher when station is -3,or floating ,obstetricians can still be optimistic towards vaginal delivery. Conclusions: Nullipara with unengaged head at term during labors should be regarded with suspicion and as such should be regarded with apprehension in labor. Dysfunctional labor occurs in only small proportion of patients with unengaged head. It is concluded that the incidence of active surgical intervention in nullipara with unengaged fetal head at term is quite high. Keywords: Primigravidae, engagement of head, delivery, LSCS, Head station